PERANAN SATGAS DALAM PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) PENANGANAN COVID-19 DI KECAMATAN SELAAWI KABUPATEN GARUT - Akbar Lucky Firdaus; Dea Apsari Pramudana Putri; Arif Farhan Suroso (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2021)
The purpose of this Field Practice Activity is to assess the efficiency of the COVID-19 task force's implementation in Selaawi District in dealing with COVID-19 and residents who have been proven positive for COVID-19. The Garut Regent's Decree establishes a Task Force for the Enforcement of Community Activity Restrictions in Selaawi District, Garut Regency. The technique that was used a Literature Review and the roadblocks that it faces, including measures to restrict the spread of the corona virus, which have not been maximized. People are progressively disobeying 3M's health recommendations, such as wearing masks, cleaning their hands with soap, and keeping a safe distance. The large-scale social restriction (PSBB) strategy has aided the implementation of physical distance in Indonesia since the start of the pandemic. The remedy to this problem is to enforce 3M (masks, distance, and hand washing) in a systematic manner, as well as passively 3T (testing, tracing, and treatment) and raise public awareness about the necessity of health procedures through the COVID-19 task force. In this method, the handling efforts can yield the best results and have been successful in lowering positive numbers and lowering deaths. Keywords: COVID-19, Emergency, Society, Implementation